School building maintenance. (Conescal, 1974)
"School buildings as a patrimoy in use by a country, are part of the goods that society appreciates mast; in that character, they must be maintained in their best conditions and obtain the highest benefits. Howeve, these buildings frequently happened to be destroyed after a short time and the community could not profit from them in the best way. Studious people of human behaviour belive that has an innate destructive impulse -in this case agiinst the school building- as a way of protest, or as a lack of discipline or simply pleasure, according to an old Freudian thesis. The fact is that schools need to be maintained and repaired, the cost of which represents an important part of any educational budget". (Copiado de la introducción).